Eggersanthus Sittichaya & Smith gen. nov., a new Oriental ambrosia beetle genus (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Sittichaya, Wisut; Smith, Sarah M. (Zootaxa, 2020)
A new genus, Eggersanthus Sittichaya & Smith gen. nov is described from a single species, Webbia sublaevis Eggers, 1927. The taxonomic characters of Eggersanthus and the morphologically similar genus Arixyleborus are analyzed and compared, and the status of the Webbia genus group is discussed.